2022
DOI: 10.1038/s41398-022-01863-8
|View full text |Cite
|
Sign up to set email alerts
|

Distinct contributions of GluA1-containing AMPA receptors of different hippocampal subfields to salience processing, memory and impulse control

Abstract: Schizophrenia is associated with a broad range of severe and currently pharmacoresistant cognitive deficits. Prior evidence suggests that hypofunction of AMPA-type glutamate receptors (AMPARs) containing the subunit GLUA1, encoded by GRIA1, might be causally related to impairments of selective attention and memory in this disorder, at least in some patients. In order to clarify the roles of GluA1 in distinct cell populations, we investigated behavioural consequences of selective Gria1-knockout in excitatory ne… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
3

Relationship

2
7

Authors

Journals

citations
Cited by 16 publications
(11 citation statements)
references
References 80 publications
2
7
0
Order By: Relevance
“…Numerous studies have shown that NMDAR dysfunction may be involved in the pathogenesis of schizophrenia and is widely associated with psychotic symptoms and cognitive impairment [44]. In addition to NMDAR dysfunction, AMPAR dysfunction mentioned in this study has been associated with selective attention and memory impairment in schizophrenia [45]. The activation of mGluR3 in the prefrontal cortex plays an important role in working memory and cognition[46], and variation in GRM3, the gene encoding mGlu3, has been shown to be associated with schizophrenia and cognitive de cits [47].…”
Section: Discussionmentioning
confidence: 58%
“…Numerous studies have shown that NMDAR dysfunction may be involved in the pathogenesis of schizophrenia and is widely associated with psychotic symptoms and cognitive impairment [44]. In addition to NMDAR dysfunction, AMPAR dysfunction mentioned in this study has been associated with selective attention and memory impairment in schizophrenia [45]. The activation of mGluR3 in the prefrontal cortex plays an important role in working memory and cognition[46], and variation in GRM3, the gene encoding mGlu3, has been shown to be associated with schizophrenia and cognitive de cits [47].…”
Section: Discussionmentioning
confidence: 58%
“…GluA1 is a postsynaptic membrane receptor mediating the glutamate signaling and synaptic function [ 37 ]; its deficiency leads to behavioral abnormalities, declined learning and memory, and impaired short-term olfaction memory [ 38 , [60] , [61] , [62] ]. Gria1 expression did not decrease after exposure to any of the three nPM batches alone.…”
Section: Discussionmentioning
confidence: 99%
“…We also found genes that regulate synapse activity, many of which have direct involvement in long-term potentiation, were upregulated; for example, Grin1/nmr-1 encodes for GluN1, an essential component of the NMDA receptor, and alternative splicing of Grin1 exon 5 controls the magnitude of long-term potentiation in CA1, and thus the ability to learn and remember (40). Gria1 encodes for the GluA1 AMPA receptor subunit, and reduction of GluA1 in CA2/CA3 impairs short-term memory (41).…”
Section: Discussionmentioning
confidence: 99%